Kritika : essays on intellectual property. - Drahos, Peter, 1955-; Ghidini, Gustavo, 1941-; Ullrich, Hanns (Kritika : essays on intellectual property,, 2015)
The fields of intellectual property have broadened and deepened in so many ways that commentators struggle to keep up with the ceaseless rush of developments and hot topics. Kritika: Essays on Intellectual Property is a series that is designed to help authors escape this rush. It creates a forum for authors who wish to more deeply question, investigate and reflect upon the evolving themes and principles of the discipline. With a view to setting in train a process of emergent critical scholarship, this inaugural volume of Kritika brings together leading scholars from the different fields of the discipline, reflecting on the private regulatory power of patents; the role of competition law in the search for the holy grail of balance in IP; the fictions of patent law; the anthropological relativism of IP; the historical transmission processes behind the IP concept; the vanishing paradigm of exclusivity in a digital environment; models of inclusive patents serving open innovation; and the rhetoric behind the copyright ratchet.